Examining the status of traditional rulers in the pre-post-colonial Yoruba society (2019)
Traditional rulers in Yoruba society have over the years played significant roles in the social, political and economic development of the traditional society. What constitutes the major roles of traditional rulers as they affect the society generally have been discussed by various scholars. However, there was little or no attention on the dwindling in Status of traditional rulers in the modern society due to modernity and civilization which has relegated them. This has over the years rendered them and the institution almost irrelevant and mere figure heads, it has also contributed in no small measure to the security threat, unbridled recklessness and instability in the nation. The paper therefore examines the change in Status and prestige of traditional rulers in the Pre and Post-colonial periods in yoruba land and how their Status could be re- invigorated and re-energized to play a complementary role in addressing various problems facing the nation today.